A STUDY ON THE ABILITY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UR IN WRITING A PARAGRAPH - Maharani, Citra Dewi; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research was conducted to find out the ability of the fourth semester students of English Study Program FKIP UR in writing a paragrafh. The sample was 60 of the fourth semester students of English study program FKIP UR which was decided by using Simple Random Sampling technique. The data were collected by giving a written test to the students. The students are expected to write a paragraph by choosing one of the given topics. The students’ score were graded by three raters and were analyzed by using Harris’ scoring system which concerned with five aspects of writing; content, form, grammar, style, and mechanics. The findings showed that there were 53 students (88%) in good level and 7 students (12%) in average level, and no student in excellent, poor and very poor level. It was also found that the students’ ability in organization aspect was the highest among the other aspects, with the average score of 69,26, while grammar aspect was the lowest one, with the average score of 63,52. Based on the result obtained, it can be inferred that the fourth semester students of English Study Program FKIP UR were able to write a paragraph and their level of ability was in good level with the average score of 67,48.This study recommended to the students to keep improving their ability and to the further study in the writing skill can focus more on how to improve students’ grammar in writing.Key words: Study, Ability, Writing, Paragraph